"LE PROPOSTE DELLA POESIA" (CONSIDERAZIONI SULLA POESIA CONTEMPORANEA ITALIANA) - Querin, Edoardo (Revista Letras, 1965)
"LE PROPOSTE DELLA POESIA" (CONSIDERAZIONI SULLA POESIA CONTEMPORANEA ITALIANA)